Addie-Based Green Synthesis Experiment Module Using Cermai Leaf Extract for 7th-Semester Students in Physics Education Program at UIN Mataram - Rizki, Dela Yunita; Meiliyadi, Lalu Ahmad Didik; Arizona, Kurniawan (Universitas Islam Negeri (UIN) Mataram, 2025)
This study aims to develop a green synthesis experimental module using Cermai leaf extract as a natural material by applying the ADDIE development model for 7th- semester students in the Physics Education Program at UIN Mataram. This study is a research and development (R&D) project comprising five stages: needs analysis, module design, product development, implementation, and formative evaluation. The subjects in this study consisted of 14 seventh-semester students as module users, as well as 3 subject matter experts and 3 media experts as product validators. The analysis results indicated the lack of an experimental module based on natural materials relevant to the concept of green synthesis. During the development stage, the module was validated by three subject matter experts and three media experts, yielding feasibility scores of 0.97 and 0.80, respectively, both falling into the “very suitable” category. A pilot test conducted among students via a response questionnaire yielded a practicality percentage of 95%, categorized as “very good.” These findings indicate that the developed module is suitable and practical for use as a physics of materials learning medium and has the potential to support environmentally friendly and contextual laboratory learning.